Protein Supplementation in Preventing and Managing Individuals with Chronic Kidney Disease - Menon Gopika S.; Shanker Niharika; Sharma Sunayan (BIO Web of Conferences)
Protein metabolism is disturbed by chronic kidney disease (CKD), a progressive illness that raises the risk of cardiovascular disease and causes metabolic problems such as inflammation and protein-energy waste (PEW). Maintaining nutritional health, lowering uremia, and slowing the course of CKD all depend on proper dietary protein control. The impact of dietary changes, such as low-protein diets (LPD) and plant-based protein sources, and protein supplements on the management of CKD are examined in this study. Research indicates that although LPD aids in the management of metabolic issues, it necessitates close observation to avoid muscular atrophy and malnutrition. While consuming too much animal protein, especially red meat, can hasten the evolution of CKD, plant-based proteins assist the kidneys by lowering acid load, phosphorus bioavailability, and uremic toxin generation. Additionally, although more research is required, LPD may improve renal protection when used with renin-angiotensin-aldosterone system (RAAS) inhibitors. Specialised nutritional techniques are needed for the management of paediatric CKD in order to balance growth and avoid malnutrition. The study emphasises the value of tailored dietary therapies and the need for more research to improve long-term dietary plans and protein consumption guidelines for individuals with chronic kidney disease.